Resveratrol Effect on Adipose-Derived Stem Cells Differentiation to Chondrocyte in Three-Dimensional Culture - Ghazal Keshavarz; Cyrus Jalili; Mona Pazhouhi; Mozafar Khazaei (Tabriz University of Medical Sciences, 2020)
Purpose: Adipose stem cells (ASCs) are pluripotent cells with the ability of self-renewal and differentiation into different types of mesenchymal cells. As cartilage repair is difficult due to lack of blood capillary, resveratrol (Res) is a polyphenolic compound with diverse biological properties to be possibly used in this case. The aim of the present study was to investigate the effect of Res on differentiation of ASCs into chondrocyte in a three-dimensional (3D) culture model. Methods: Subcutaneous adipose tissues were prepared and digested enzymatically, and passed through cell strainer. ASCs were harvested in the fourth passage, and divided into five groups. The control group received chondrogenic differentiation medium (CDM) while the experimental groups received CDM plus different doses of Res (1, 10, 20, and 50 µM) for 21 days. Expression of cartilage specific genes and Sirtuin1 (SIRT 1), cell viability, apoptosis and ferric reducing antioxidant power (FRAP) were detected using reverse transcription polymerase chain reaction (RT-PCR), MTT assay, TUNEL and acridine orange/ethidium bromide (AO/EB) staining. One-way ANOVA and non-parametric Mann-Whitney U test were used for data analyses. Results: ASCs were differentiated to chondrocyte by CDM in a three-dimensional culture. 10 and 20 µM doses of Res showed the most proliferating effect on ADSCs. The SIRT 1 genes expression and FRAP level also increased significantly compared to the control group (P<0.05). Also, OD of cell increased whereas apoptosis decreased. Conclusion: 3D culture was a suitable condition for ASCs differentiation to chondrocyte, and lower doses of Res exert proliferation effect on ASCs.